PERTUMBUHAN BIBIT KELAPA SAWIT DI PRE-NURSERY DENGAN KOMPOSISI MEDIA TANAM DAN KONSENTRASI PUPUK CAIR Azolla pinnata BERBEDA - Filsafat Waruwu; Bilman Wilman Simanihuruk; Prasetyo Prasetyo; Hermansyah Hermansyah (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2018)
[GROWTH OF OIL PALM SEEDLINGS IN PRE-NURSERY UNDER DIFFERENT MEDIA COMPOSITIONS AND CONCENTRATIONS OF Azolla pinnata LIQUID FERTILIZER]. Vigourous seedling is prerequisite to successful production of oil palm. Aside from the genetic quality of the planting material, supply of nutrients during early growth of the seedling play an important role in determinting the overall seedling performances. This study was performed to determine the best combination of media composition and concentration of liquid fertilizer made of Azolla pinnata for oil palm seedling growth during pre-nursery. A factorial arrangement of the treatments involving growing media consisted of different composition of oil palm empty fruit bunches compost and soil (1: 1, 1: 2, and 2: 1 v/v) and different concentration of Azolla pinnata liquid fertilizer applications (0, 20, 40, and 60 mL/L) were arranged in a randomized complete block design with three replications. Data were collected for leaf number, stem diameter, seedling height, and leaf greenness at 30, 60, and 90 days after sowing (DAS). A significant interaction effect between the treatments was observed on leaf number at 60 and 90 DAS. A further regression analysis revealed that the highest number of leaves (4.3 at 60 DAS and 6.9 at 90 DAS) were attained on the media composition of 1:1 with liquid fertilizer application at 37.5 and 56 mL/L, respectively. Seedling height and stem diameter at 90 DAP showed quadratic responses to the increasing concentration of the liquid fertilizer applications. The maximum seedling height (26.22 cm) was attained at the liquid fertilizer concentrations of 36.21 mL/L. Similarly, the maximum stem diameter (7.43 mm) was attained at the concentration of 51.00 ml/L. The leaf greeneess at 60 DAS was increased in a linear fashion with the increasing concentration of the liquid fertilizer.